2013
DOI: 10.1002/ajpa.22402
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic scaling of the human nose in a longitudinal sample: Implications for genus Homo facial evolution

Abstract: Researchers have hypothesized that nasal morphology, both in archaic Homo and in recent humans, is influenced by body mass and associated oxygen consumption demands required for tissue maintenance. Similarly, recent studies of the adult human nasal region have documented key differences in nasal form between males and females that are potentially linked to sexual dimorphism in body size, composition, and energetics. To better understand this potential developmental and functional dynamic, we first assessed sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
87
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 52 publications
11
87
2
Order By: Relevance
“…Several recent studies (Bastir et al, 2011;Bastir & Rosas, 2016;Holton et al, 2014Holton et al, , 2016aHolton et al, , 2016bRosas & Bastir, 2002) have demonstrated a strong relationship between volumetric oxygen intake requirements and height dimensions of the nasal complex. Several recent studies (Bastir et al, 2011;Bastir & Rosas, 2016;Holton et al, 2014Holton et al, , 2016aHolton et al, , 2016bRosas & Bastir, 2002) have demonstrated a strong relationship between volumetric oxygen intake requirements and height dimensions of the nasal complex.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent studies (Bastir et al, 2011;Bastir & Rosas, 2016;Holton et al, 2014Holton et al, , 2016aHolton et al, , 2016bRosas & Bastir, 2002) have demonstrated a strong relationship between volumetric oxygen intake requirements and height dimensions of the nasal complex. Several recent studies (Bastir et al, 2011;Bastir & Rosas, 2016;Holton et al, 2014Holton et al, , 2016aHolton et al, , 2016bRosas & Bastir, 2002) have demonstrated a strong relationship between volumetric oxygen intake requirements and height dimensions of the nasal complex.…”
Section: Discussionmentioning
confidence: 98%
“…According to our developmental simulations the Inuit show a more pronounced development in the nasal aperture compared to the Khoisan, possibly related to their colder habitat conditions. Anterior facial growth has been linked to the development of the nasal cavity and the respiratory system (Enlow, 1990;Bastir, 2008;Bastir et al, 2011;Holton et al, 2014). Differences in nasal cavity form have been shown to be climatic adaptations involving the need to heat and humidify respired air (Proetz, 1953;Carey and Steegmann, 1981;Franciscus and Trinkaus, 1988;Noback et al, 2011), and studies indicate that male-female differences in nasal size and shape is a sexual dimorphic feature appearing during adolescence (Rosas and Bastir, 2002;Hall, 2005;Bastir et al, 2011;Holton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior facial growth has been linked to the development of the nasal cavity and the respiratory system (Enlow, 1990;Bastir, 2008;Bastir et al, 2011;Holton et al, 2014). Differences in nasal cavity form have been shown to be climatic adaptations involving the need to heat and humidify respired air (Proetz, 1953;Carey and Steegmann, 1981;Franciscus and Trinkaus, 1988;Noback et al, 2011), and studies indicate that male-female differences in nasal size and shape is a sexual dimorphic feature appearing during adolescence (Rosas and Bastir, 2002;Hall, 2005;Bastir et al, 2011;Holton et al, 2014). That is males have a higher daily energy expenditure, greater respiratory air consumption and larger body mass and consequently a larger nasal size from adolescence onward (Bastir et al, 2011;Holton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals a higher frequency of bleeding in women than in men. This may originate in anatomical differences of the nasal cavity between males and females [6]. Dumortier et al.…”
Section: Discussionmentioning
confidence: 99%